Numerical investigations on oscillating aspirations controlling separation flows in linear highly loaded compressor cascades - Liu, Bao; Cai, Le; Xu, Hao; Fu, Haiyan; Wang, Songtao (Frontiers in Energy Research, 2022)
Vortex separation structures in linear compressor cascades controlled by the boundary layer oscillating suction (BLOS) are numerically investigated. The oscillation parameters (Amplitude and Frequency) and the suction control parameters (Position and Mass) are continuously adjusted. It is found that introducing unsteady excitations with proper frequencies into the steady aspiration results in a more effective control effect. The BLOS not only alleviates the separation by removing low-energy fluid, but also optimizes the vortex shedding process to help reduce losses.